PENGARUH MODEL PEMBELAJARAN INQUIRY TERBIMBING TERHADAP KETERAMPILAN BERFIKIR KRITIS SISWA KELAS V SD AL MANAR SURABAYA - Lita Aditya Khoirun Nisa; Aminatul Julfaidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research seeks to assess how guided inquiry learning models impact the critical thinking abilities of fifth graders at SD Al Manar Surabaya, focusing on the characteristics of geometric shapes. Quantitative approach is employed with a quasi-experimental format. The study's participants are all fifth-grade pupils at SD Al Manar Surabaya. The research sample includes 25 learners from class VA serving as the control group, alongside 25 learners from class VB who make up the experimental group. For data collection, the study utilized interviews, observations, tests targeting critical thinking skills, and documentation. The study concentrated on the results of tests, which were assessed for normal distribution, consistency, and independent sample t-tests to examine the suggested hypotheses. The data analysis was performed with IBM SPSS Statistics version 26. The outcomes of the hypothesis tests, obtained from the independent sample t-test, showed a significance (2-tailed) value of 0. 015.